A study of factors affecting attitudes after visiting eco-tourism destination Don Hoi Lot, Samut Songkhram - Rumpapak Luekveerawattana (Cogent Social Sciences)
This research aims to study the factors influencing post-visit attitudes towards ecotourism destinations. A quantitative research approach was employed, involving the distribution of structured questionnaires to a sample of 401 tourists and visitors at a designated ecotourism site. The sample was selected using systematic sampling to ensure representativeness. The questionnaire was carefully designed and pre-tested, achieving a high-reliability score with a Cronbach’s alpha coefficient of 0.85, indicating internal consistency. The data were analyzed using descriptive statistics, including frequencies, percentages, means, and standard deviations. Furthermore, path analysis was employed for hypothesis testing to determine the relationships between key variables. This comprehensive analysis identified spatial (X1) and participation factors (X4) as the primary influencers of post-visit attitudes at the ecotourism destination.